If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(x + 5) + -6 = 0 Reorder the terms: 3(5 + x) + -6 = 0 (5 * 3 + x * 3) + -6 = 0 (15 + 3x) + -6 = 0 Reorder the terms: 15 + -6 + 3x = 0 Combine like terms: 15 + -6 = 9 9 + 3x = 0 Solving 9 + 3x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + 3x = 0 + -9 Combine like terms: 9 + -9 = 0 0 + 3x = 0 + -9 3x = 0 + -9 Combine like terms: 0 + -9 = -9 3x = -9 Divide each side by '3'. x = -3 Simplifying x = -3
| 7x+2z=8+8y | | ln(x+14)-ln(8-3x)=3ln(2) | | 8=-116+n | | lnx+ln(x-2)=2ln(x-3) | | (7/10)-(8/15) | | 4(7i-5)=6(4i-2) | | 11/16-1/48 | | 1/48-11/16 | | -10x+5=7x+5 | | 4x+7=6-24x+36 | | 43/30 | | f(t)=0.2t^2+0.03t^3 | | 57=(x+2)x | | (5-u)(5u-6)=0 | | 3x-3+2x=52 | | -4(y+1)(-y+6)=0 | | 3(2f+5)=5(f+1) | | 7=-0.5x^2+27.25 | | (4w-2)(8+w)=0 | | 6(4c-3)+2(2-c)= | | 16a-7a= | | 2a=5x-5y | | 4x+1-7x=16 | | 3/5y=x | | 6(3h-5)=7(3h-2) | | -4(3y-8)+2(2y+10)= | | -24=-6w+3(w-7) | | 2-3*(x-1)*(x-1)=0 | | (5x/2)-9=0 | | 8*(8b/8) | | 10x^4+28x^3-6x^2=equa | | x=0.625+0.625y+-0.625z |